(3GdahGFO GdSfjI aj EYQGH CeKdI GdCLQhejIs - (3GdTGaYqj GdaQVqj, GdfLe, eMeO Hf jMji Hf Jbj GdOjf Hf YHGOI, (B1090 (3g`s ((3eOjfI YLdhfs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bhd GdBLQhej GdcdGe gh GddaX GdeQcH GdeajO HGdhVY GdcdGe dg eYfjGf eYfi aj GddZI heYfi aj GdGUWdGMs
(3BNQgG (B:s
(3YdGeI LQg GdjGA fjGHI Yf GdcSQI dCfg ef GdCSeGA GdNeSI hgh eVGa hGdcGa VejQ eJUd aj eMd LQ HGdEVGaIs
(3aj BNQg fbhd aj GdfMh ef b(B67 - (3b(B75 (3hgj fbhd HGddZI GdYQHjI hGdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 141s
(3eYLe GdeDdajf(B: 3 / 765s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs